Feasibility of an Online Delivered, Home-Based Resistance Training Program for Older Adults – A Mixed Methods Approach - Vikberg, Sanna; Björk, Sabine; Nordström, Anna; Nordström, Peter; Hult, Andreas (Frontiers in Psychology, 2022)
Background: Physical inactivity and low muscle mass are risk factors for falls, fractures and overall poor health. However, physical activity is reduced with increased age and only a fraction of older adults engages in resistance training (RT). Thus, strategies that facilitate RT among older adults are needed. The aim of the present study was to evaluate the effectiveness and user experience, and explore barriers and motivators towards an online delivered, home-based RT program in older adults with low muscle mass. Methods: Thirty men and women, 70-71 years of age with low muscle mass were assigned home-based RT with online exercise videos (3 times/week, 45 min/session for 10 weeks) accompanied with an initial supervised try-out session. Quantitative outcome measures included changes in lean body mass and physical function. Semi structured one-to-one interviews with a subset of the participants (n=8) were also conducted to generate a greater understanding of the participants experience of the digitally supported RT. The material was transcribed and analysed with qualitative content analysis. Results: Twenty-seven participants (90%) completed the trial. Lean body mass increased by 0.39 kg (95%CI; 0.06-0.72, p<0.05) and chair stand time improved by 1.6 seconds (95%CI; 0.8-2.3, p<0.001). No significant improvements were seen for balance or gait speed. The theme “Engaging in Digital Resistance Training with Personal Adaptation Leads to a Sense of Strength and Vitality” captured the participants experience of the intervention, where a sense of how the body was changing towards a more active lifestyle was described. Instructions, feedback, and intrinsic motivation were identified as key elements for compliance. Conclusions: The online delivered RT program for older adults with low muscle mass was feasible based on high compliance, user satisfaction, increased lean mass and improved physical functionchair-stand time. The participant experiences may explain the high compliance to the intervention and effects on outcomes. Based on these results, online delivered RT could be an accessible exercise routine for older adults with low muscle mass. More research is needed to verify the present findings and assess changes in a long-term perspective.